Austerity effects on national output and income inequality: A systematic literature review - Okeke, Angela; Alexiou, Constantinos; Nellis, Joseph G. (De Gruyter, 2021)
Fiscal sustainability issues over rising national debt concerns and the consequent expansionary fiscal retrenchment hypothesis has fuelled the contentious austerity vis-à-vis stimulus debate which has spawned a large empirical literature of conflicting findings on the economic effects of austerity – with particular emphasis revolving around equity and distributional issues. In this paper we attempt to summarise the growing literature on the recent developments regarding the theoretical as well as empirical approaches on national output and distributional aspects of austerity. By exploring the existing evidence in the literature on the effect of consolidation programs, we offer a more holistic overview of the subject matter through a synthesis of the extant literature and, by so doing, propose directions for future research pertinent to both academic researchers and policymakers.
Keywords: fiscal austerity; inequality; income distribution; systematic literature review